Description of Knowledge and Age of Couples of Reproductive Age Using Long-Term Contraception Methods in Kunden Hamlet, Sendangsari Village - Olivia Laora Todang; Retno Heru Setyorini; Riadini Wahyu Utami; Ari Andriyani (CV. Rayyan Dwi Bharata, 2024)
Government policy in order to reduce the rate of population growth is the Family Planning (KB) movement. The longterm contraceptive method (MKJP) has a high level of effectiveness in minimizing the number of births. This method can be used for a long period of time, can reduce birth rates or terminate pregnancy. The purpose of this study was to determine the relationship between the level of knowledge about MKJP and age with the use of long-term contraceptive methods. The method used in this research is to use descriptive method. The population used in this study were couples of childbearing age who live in Kunden Hamlet. Sampling in this study using probability sampling technique based on inclusion and exclusion criteria amounted to 74 respondents. The research instrument used was a questionnaire distributed to respondents. Data analysis is presented in the frequency distribution table. The results of this study found that most of the respondents had a relatively low level of knowledge, namely 50 respondents (67.6%) and the other 24 respondents (32.4%) had a sufficient level of knowledge. Based on frequency distribution data, only 2 respondents (28.6%) were aged 20 years old using long-term contraception methods (28.6%), 4 respondents were aged 20-35 years (57.1%) and those aged 35 years were only amounted to 1 respondent (14.3%). So it can be concluded that the description of knowledge about long-term contraceptive methods is in the less category. While the age is dominated at the age of 20-35 years.